Cortical microcystic disease of the kidney with dominant inheritance: a previously undescribed syndrome. - Melnick, S C (1984)
We report a family in which the father and all three children had symptomless chronic renal failure and, in the case of the children, normocytic, normochromic anaemia. None had hypertension, proteinuria, or abnormality of urinary deposit. Renal biopsy specimens showed microcysts confined to the renal cortex; some cysts contained vestigial glomerular tufts. This family appears to represent the first known example of hereditary cortical microcystic disease. The distribution of the disease suggests dominant inheritance without sex linkage.